Evaluation Of Internal Control System In Cash Receipt Accounting Information System At Laboratory Clinic “XY” Branchsemarang - Diah Kurnia Sari; Andalan Tri Ratnawati (Universitas Kristen Indonesia Toraja, 2022)
This research aims to determine the evaluation of internal control in the cash receipts accounting information system carried out by the company and the problems faced in evaluating the internal control system in the cash receipts accounting information system at the